1998
DOI: 10.1080/00221689809498637
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical validation of the dead-zone model for longitudinal dispersion in rivers

Abstract: Experimental results of longitudinal dispersion in rivers are discussed in the light of new findings with respect to the "dead-zone" theory. Both the experiments made by authors as well as some literature results are taken into consideration. The dead-zone model parameters, namely the relative dead-zone volume, penetration time of the tracer into dead-zones, constant mean flow velocity and dispersion coefficient, are obtained with the use of the nonlinear least square technique applied to the image functions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 15 publications
2
35
0
Order By: Relevance
“…The total friction factor is extremely difficult for evaluation with the available data, the achieved error is unacceptable and it makes the method inapplicable in most cases. In certain situations it might lead to similar results to those obtained by means of other techniques (see Czernuszenko et al, 1998), but it requires a very good knowledge of the stream characteristics. Therefore, even the results based on the SY method, also dependent on friction factor f, are only to illustrate the possible differences introduced by different methods.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The total friction factor is extremely difficult for evaluation with the available data, the achieved error is unacceptable and it makes the method inapplicable in most cases. In certain situations it might lead to similar results to those obtained by means of other techniques (see Czernuszenko et al, 1998), but it requires a very good knowledge of the stream characteristics. Therefore, even the results based on the SY method, also dependent on friction factor f, are only to illustrate the possible differences introduced by different methods.…”
Section: Resultssupporting
confidence: 57%
“…The database used in this paper was put together by Cheong & Seo (2003). They collected the measurements from the studies of Fisher (1968), Godfrey & Frederick (1970), Nordin & Sabol (1974), Graf (1995) and Czernuszenko et al (1998). The database is composed of 58 measurements, obtained for river reaches which vary significantly in time and space scales, as well as in hydrological regime.…”
Section: Databasementioning
confidence: 99%
“…Exchange between streams and groundwater aquifers has Rowinski, 1997;Czernuszenko et al, 1998]. A new model explicitly represents stream-subsurface exchange as a diffusive process [Worman, 1998] but still requires curve fitting to determine the exchange coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…After the introduction of the TSM, transient storage processes have been studied in a variety of small mountain streams, as well as large rivers, and it was shown that simulation results of tracer study data considering the transient storage impact have good agreement with observed data. Also, it was shown that the interaction between the main channel and storage zones, especially in mountain streams, has a great effect on solute transport behavior (D'Angelo et al, 1993;DeAngelis et al, 1995;Morrice et al, 1997;Czernuszenko et al, 1998;Chapra and Runkel, 1999;Chapra and Wilcock, 2000;Laenen and Bencala, 2001;Fernald et al, 2001;Keefe et al, 2004;Ensign and Doyle, 2005;Van Mazijk and Veling, 2005;Gooseff et al, 2007;Jin et al, 2009). In this study, a comprehensive model, called TOASTS (third-order accuracy simulation of transient storage), able to obviate shortcomings of current models of contaminant transport, is presented.…”
Section: Introductionmentioning
confidence: 99%